(untitled) (Global Journal of Science Frontier Research, 2017)
Female and male individuals of Amphimermis thezamica sp. n. (Nematoda: Mermithidae) have been described. The host organism is unknown. The material was collected from the soil of private gardening plot, located in village Tezami of Mtskheta-Mtianeti Region (East Georgia). A new species is characterized by the combination of the following features: amphids cup-shaped, less oval and with average size, vagina prolonged, S-shaped, round eggs with smooth surface and thick envelope, 56 papillae, arranged in three rows in genital part, long double spicule, intertwined in some sections. By morphological and morphometric data a new species is close to the group of A. bogongae, especially to A. litoralis. New species resembles A. litoralis by the shape of amphids, S-shaped vagina, ending of a tail and twisted spicule. It differs from A. Litoralis by the length of vagina, structure of spicule and twisted parts, presented in its different sections, by the length of twisted and untwisted parts; by the shape of stoma.